HISTOPATHOLOGICAL SPECTRUM OF RENAL LESIONS IN POST NEPHRECTOMY SPECIMENS: AN AUDIT IN BURDWAN MEDICAL COLLEGE AND HOSPITAL. - Dr Susanta Kumar Das; Dr. Koushik Bose; Dr. Anushila Roy (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
: Nephrectomy is a surgical procedure for certain renal pathologies that include a wide spectrum of non-neoplastic and neoplastic entities, ranging from inflammatory conditions like pyelonephritis to malignant neoplasms such as renal cell carcinoma (RCC). Histopathological examination is the gold standard for definitive diagnosis and classification.Aims and Objectives: To study the clinicopathological profile of renal lesions over a six-year period in a tertiary care hospital in West Bengal Methods: This was a hospital based retrospective descriptive study conducted over six years, including 65 nephrectomy specimens. Clinical data, gross morphology, and histopathological specimens were reviewed. The lesions were categorized into non-neoplastic (inflammatory and degenerative) and neoplastic groups (benign and malignant).Results: Among 65 renal specimens analyzed, 38 cases (58.5%) were neoplastic and 27 cases (41.5%) were non-neoplastic. The neoplastic category was dominated by renal cell carcinoma (RCC), comprising 34 cases (52.3%), of which clear cell RCC accounted for 25 cases (73.5%), papillary RCC for 5 cases (14.7%), and chromophobe RCC for 4 cases (11.8%). Non-neoplastic lesions included chronic pyelonephritis (14 cases), hydronephrosis (6 cases), xanthogranulomatous pyelonephritis (3 cases), and advanced chronic kidney disease-related changes (4 cases). The age range of patients was 25–80 years, with a mean age of 52.4 years. Males predominated with a male-to-female ratio of 1.4:1. The left kidney was slightly more involved (56.9%) than the right (43.1%). Most RCC cases presented at stage pT1–pT2, with Fuhrman Grade 2 being most frequent.Conclusion: This study provides a detailed histopathological spectrum of nephrectomies performed at our institution hence provides a reflection of the clinical spectrum in this part of the country. Non-neoplastic inflammatory lesions continue to form a significant proportion of renal pathology. However, renal cell carcinoma, particularly the clear cell subtype, remains the most common malignant lesion. Histopathological evaluation is crucial for accurate diagnosis, subclassification, and grading, directly influencing management and prognosis. In developing countries benign diseases are more common than malignancies.